Hematological Parameters in Subchronic Toxicity Test of Black Garlic Ethanol Extract in Rats - Ellen Stephanie Rumaseuw; Yoppi Iskandar; Eli Halimah (Universitas Muhammadiyah Yogyakarta, 2022)
The community has used black garlic since ancient times for hypercholesterolemic. Until now, people still consume both raw and cooked black garlic. Black garlic is included in processed garlic products. People on the Asian continent have used black garlic for the past 10 years. This study aims to determine the sub-chronic toxic effect of black garlic ethanol extract on male and female white rats using hematological parameters consisting of hematocrit, hemoglobin, erythrocytes, leukocytes, platelets, MCV, MCH, and MCHC. This research method was a completely randomized design with the administration of ethanolic extract of black garlic to rats in 5 treatment groups, including a negative control group, a dose group of 1000 mg/kg BW, a dose group of 2000 mg/kg BW, a negative control satellite group and a satellite group with a dose of 2000 mg/kg BW. Data were analyzed statistically using one-way ANOVA with a 95% confidence level and SPSS version 20. The study results of black garlic ethanol extract showed no significant effect or were at normal levels on hematological parameters. Therefore, it can be concluded that the ethanolic extract of black garlic is safe for human use as a treatment for hypercholesterolemia.